2015
DOI: 10.2139/ssrn.2594985
|View full text |Cite
|
Sign up to set email alerts
|

Hotels vs. Peer-to-Peer Accommodation Rentals: Text Analytics of Consumer Reviews in Portland, Oregon

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 22 publications
4
52
0
Order By: Relevance
“…They perceive their Airbnb place as a home away from home. Similar results were also found by Tussyadiah & Zach [51] and Belarmino et al, [4]. According to them, Airbnb customers value the most the social interaction with the host and the characteristics of István Egresi, Viorel Puiu, Vasile Zotic, Diana Alexandru Attributes that contribute to guest satisfaction: a comparative… the neighborhood.…”
Section: Table 1 Main Attributes That Determine Guest Satisfaction (supporting
confidence: 77%
See 3 more Smart Citations
“…They perceive their Airbnb place as a home away from home. Similar results were also found by Tussyadiah & Zach [51] and Belarmino et al, [4]. According to them, Airbnb customers value the most the social interaction with the host and the characteristics of István Egresi, Viorel Puiu, Vasile Zotic, Diana Alexandru Attributes that contribute to guest satisfaction: a comparative… the neighborhood.…”
Section: Table 1 Main Attributes That Determine Guest Satisfaction (supporting
confidence: 77%
“…This makes any attempt to compare in this format the main attributes of satisfaction as identified by guests of hotels and Airbnb accommodations very difficult. More recently, a number of studies have attempted to compare the main accommodation attributes that generate satisfaction for Airbnb and hotel customers [4], [5], [17], [32], [33], [50], [51]. The results of these studies show that some attributes are common for both forms of accommodation, such as clean rooms and comfortable beds [51].…”
Section: Table 1 Main Attributes That Determine Guest Satisfaction (mentioning
confidence: 99%
See 2 more Smart Citations
“…Belarmino, Whalen, Koh, and Bowen (2017) examined user-generated comments to compare P2PA and traditional hotel reviews in the United States and found that P2PA guests emphasize relationships with hosts and hotel guests place more values on room attributes. Tussyadiah and Zach (2015) compared the service attributes of hotels and P2PA in Portland, Oregon, and found that hotels' main competitive advantage is the convenience of their services and that the main motivations for choosing P2PA are personal and social (Tussyadiah & Zach, 2015). In addition, P2PA can provide more authentic travel experiences, which increases both travel frequency and length of stay at a destination (Tussyadiah & Pesonen, 2015).…”
Section: Previous Studies Of P2pamentioning
confidence: 99%